Reduced Occurrence of Gastrointestinal Symptoms in Chinese Infants Fed Minimally Processed Commercially Available Formula: A Cross-Sectional Observational Study. (25th March 2020) - Sheng, Xiao Yang; Buthmanaban, Vanitha; van Lieshout, Glenn A. A.; Parikh, Panam
Abstract : Healthy Chinese infants consuming one of four commercially available infant formulas (IF) were assessed on the occurrence of gastrointestinal symptoms associated with suboptimal digestion of processed milk proteins. The IF differed in blocked lysine (BL) levels, a proxy indicator of heat processing as well as the nutritional quality of milk. A cross-sectional, observational study of one week was conducted in healthy, term, exclusively formula-fed Chinese infants ( n  = 452) fed with one of four commercially available IF (IF A n  = 106, BL 9%; IF B n  = 119, BL 12%; IF C n  = 113, BL 11%; IF D n  = 114 BL 20%). Parents/caretakers were requested to report feeding quantity, gastrointestinal symptoms, crying behavior, and stool characteristics daily using subject dairy and Amsterdam Infant Stool Scale (AISS). Infants fed with IF A reported less "hard" and "watery" stools and more "soft/formed" stools. Higher percentages of score I (yellow/golden) or II (orange) and less green (score III) coloured stools were noted for IF A-fed infants compared to all other formulas according to AISS. Night time crying was also significantly lower in the IF A groups compared to all other formulas. Furthermore, a higher percentage of parents/caretakers of IF A-fed infants reported absence or no complaints of abdominal distension, burping, flatulence, diarrhea, and constipation. Results suggest lower occurrence of GI symptoms and lower crying time at night in infants fed with minimally processed formula (indexed by BL levels). Future studies are required to confirm the association between minimal processing of milk formula and improved gut comfort in healthy infants.